CONCILIATOR VS BLOC LEADER : PERBANDINGAN KEBIJAKAN BARACK OBAMA & DONALD TRUMP DALAM MERESPON PERTUMBUHAN EKONOMI CHINA - Zubaidah, Ainun Arta; Herningtyas, Ratih (Jurnal Ilmiah Widya Sosiopolitika; Vol 3 No 2 (2021): MEDIA, POLITIK, DAN PANDEMIDO - 10.24843/JIWSP.2021.v03.i02.p05, 2021)
ABSTRACT Since the fall of the Berlin Wall in 1989, the United States has become the world's undisputed economic superpower. However, the economic reforms carried out by China since the 1980s have had a big effect on its economic growth, so that it is able to rank as the second largest economy in the world after the United States. This makes America must respond to China's development by making strategic policies. State leaders have an important role in determining the direction of United States Foreign Policy. From 2009 to 2018, America underwent 2 transitions of leadership, namely from President Barack Obama to being replaced by President Donald Trump. Even though the two leadership eras are close together, the US Foreign Policy towards China is in stark contrast. This research will analyze how the differences in the US Foreign Policy against China in the Barack Obama and Donald Trump Era and the factors that cause differences in their policies by using the idiosyncratic individual factor approach. This article finds that the different backgrounds in the life of a country's leader will influence their perception in determining the direction of their foreign policy. Key words: U.S. Foreign Policy, China, Barack Obama, Donald Trump, Idiosyncratic, Psychobiography